Is Organizational Culture Mediating The Relationship Recruitment And Placement On Employee Performance In Bhirawa Daily Newspaper Office? - Samuel Budi Nugraha; Tatik Suryani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
Many research focus on the effect of recruitment and placement on employee performance, but less of them focus for examining the role of organizational culture as mediator for stimulating employee performance. The purpose of this study was to examine and analyze the effect of recruitment, placement, and organizational culture on employee performance at the Daily newspaper Bhirawa Surabaya Company. In this research also examine the role of organizational cultue as the mediator in that relationship on both variables on employee performance. The research was conducted by using a survey design with sensus for collecting data. Questionnaires which is designed by Likert scale were used to collect data. Data was analyzed with Partial Least Square. The results of this study indicate that recruitment has no positive effect on employee performance, placement has no positive effect on employee performance, organizational culture has a significant effect on employee performance and organizational culture mediates the effect of recruitment on the employee’s performance of daily newspaper Bhirawa Surabaya. Keywords : Recruitment, Placement, Organizational Culture, Employee Performance